AVALIAÇÃO DO EXTRATO AQUOSO DE HANDROANTHUS HEPTAPHYLLUS (MART.) MATTOS NA LIPOPEROXIDAÇÃO EM TECIDOS DE RATOS WISTAR DIABÉTICOS - Goettems, Pauline B.; Salamoni, Bethânia; Jr, Paulo I. H. d. B.; Rhoden, Cláudia R.; Heck, Thiago G.; Ludwig, Mirna S. (Salão do Conhecimento, 2013)
Resumo